用于导管的多功能导电元件 (2023)
本发明题为："用于导管的多功能导电元件"。本发明的所述实施方案包括一种设备，所述设备包括配置成用于插入对象身体内的可扩展结构，以及耦合到所述可扩展结构的多个导电元件。所述导电元件中的每个导电元件包括相应的线圈，并且具有与所述对象的组织电绝缘的绝缘部分以及配置成在与所述组织接触时与所述组织交换信号的未绝缘部分。还描述了其它实施方案。 Described embodiments include an apparatus that includes an expandable structure, configured for insertion into a body of a subject, and a plurality of conducting elements coupled to the expandable structure. Each of the conducting elements comprises a respective coil and has an insulated portion that is electrically insulated from tissue of the subject, and an uninsulated portion configured to exchange signals with the tissue, while in contact with the tissue. Other embodiments are also described.